2015
DOI: 10.1515/jpem-2013-0495
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D status and its associations with components of metabolic syndrome in healthy children

Abstract: The prevalence of low vitamin D level in the studied healthy children was high and it is correlated with some components of metabolic syndrome. Outdoor activity for optimum sun exposure and additional studies are needed to evaluate the underlying metabolic syndrome components and hypovitaminosis D complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 18 publications
4
13
2
1
Order By: Relevance
“…A study in healthy Iranian children reported a significantly higher prevalence of vitamin D deficiency in girls than boys (42.9% vs. 16.4%, respectively) (21). In this study we did not observe any demographic or clinical risk characteristics for low vitamin D level except for the difference between sites which might be explained by geographic, cultural, and nutritional factors.…”
Section: Discussioncontrasting
confidence: 70%
“…A study in healthy Iranian children reported a significantly higher prevalence of vitamin D deficiency in girls than boys (42.9% vs. 16.4%, respectively) (21). In this study we did not observe any demographic or clinical risk characteristics for low vitamin D level except for the difference between sites which might be explained by geographic, cultural, and nutritional factors.…”
Section: Discussioncontrasting
confidence: 70%
“…In fact, particularly obesity has been independently associated with low 25(OH)D levels and dyslipidemia [2,8]. Nevertheless, different authors have described-as it occurred in this study-the existence of an association between Vitamin D status and lipid profile in children and adolescents [15,[25][26][27].…”
Section: Discussionmentioning
confidence: 49%
“…It is estimated that more than 1 billion people have suffered from VDD [7]. VDD causes a variety of disorders that include but are not limited to calcium and phosphorus metabolism disorder, infection, autoimmune disease, tumours and allergic disease [8-10]. A potential link between VD and the development of allergic disease (the so-called “vitamin D hypothesis”) first emerged when higher rates of allergic disease were observed in people residing at higher latitudes, where VDD is common [11].…”
Section: Introductionmentioning
confidence: 99%